RANCANG BANGUN SISTEM FILTRASI OTOMATIS SERTA MONITORING PH DAN SUHU AIR BERBASIS IOT UNTUK AKUARIUM IKAN CUPANG - Bono Badar Nugraha; Ponco Siwindarto; n/a Nurussa’adah (Jurnal Mahasiswa TEUB, 2023)
Betta fish is one of the ornamental fish that is quite easy to maintain and is one type of ornamental fish that has high economic value and widely sold in the market. To maintain the quality of water in the betta fish aquarium is done by manually changing the water every few days. The life of ornamental fish in an aquarium is strongly influenced by how the water quality in the aquarium.Water quality can be defined by the value of several aspects such as acidity(pH) and temperature. The use of microcontrollers to perform automation and IoT that can be used to exchange information directly by relying on the use of the internet is a solution to the problem of fish owners. Therefore, this research designs an automatic filtration system as well as IoT-based pH and temperature monitoring for a betta fish aquarium using an Arduino Uno microcontroller, pH sensor, temperature sensor, water level sensor, water pump and NodeMCU. Tests are performed on each sensor and device required as well as testing the automation of the entire system. Based on the test results, the pH sensor has a range of differences in reading values against a pH meter of 0.58% to 1.41%, the DS18B20 temperature sensor has a range of differences in reading values against a digitalthermometer of 0.63% to 1.96% and, the HY-SRF05 water level sensor has a range of differences in reading values against a ruler of 1.38% to 6.10%. In testing the water pump using a relay, it can work according to the input given from the microcontroller. Sensor data transmission on smartphones via the internet with NodeMCU intermediaries shows the similarity of sensor readingdata values with smartphone displays. The test results show that the automatic filtration system and IoT-based pH and temperature monitoring for the betta fish aquarium can work as expected. Key words: Parrot fish, filtration, pH, temperature, IoT